A guerra e o mar especulações sobre o pensamento político de Peter Sloterdijk - Liron, Eduardo Henrique Annize (2016)
This work investigates some themes of political philosophy developed by the German thinker Peter Sloterdijk, namely the ones related to the establishment of collective belonging ties, and social mechanisms of speech and hearing in the public sphere, as instances creating inhabitable worlds for humans. We will review several of his texts, from Critique of Reason Cynical to "The revolution of the giving hand", heuristically collecting formulations and discussions that allow us to propose a reading of his political thought as a battle for the possibilities of being in the world. In this scenario we will try to explain certain aspects of his thought on the existence in terms of spherology, that means, from the political-psychological perspective that derives from the relations between the principles of anthropotechnics and thymotics. At the same time, considering that Sloterdijk’s thought on the coming into being results from a process of constituting oneself in reference to a set of social and historically determined practices, we will apply these tools to explicit some aspects of Sloterdijk’s reading of this government of the many, which we call today by the name of representative democracy, especially through the processes of creation of both belonging ties and possibilities of existence